2017
DOI: 10.1093/aje/kwx132
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Antioxidant Vitamins and Carotenoids and Risk of Developing Active Tuberculosis in a Prospective Population-Based Cohort Study

Abstract: Antioxidants may protect against oxidative stress, which is associated with tuberculosis (TB) disease. However, direct evidence for a protective association between dietary antioxidants and TB incidence in humans has been lacking. The relationship between intake of antioxidant vitamins (vitamins A, C, D, and E) and individual carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein) and TB incidence was examined in the Singapore Chinese Health Study, a prospective cohort study of 63,257 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms . Interestingly, obesity appears to protect against development of TB .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms . Interestingly, obesity appears to protect against development of TB .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“…83 Some micronutrients are possibly of importance in protecting against reactivated TB, through anti-oxidative and other mechanisms. 84,85 Interestingly, obesity appears to protect against development of TB. 86 The relevance of nutritional attention in preventing and managing TB is likely to be highest in geriatric patients, and more research appears warranted.…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“… 31–33 Hence, in this study that focused on the effect of alcohol consumption on active TB risk, we had included all these previously described factors as covariates in the model. Furthermore, since cigarette smoking is an established and strong risk factor of active TB and we had previously described the differential effects of vitamin C intake on the risk of active TB among smokers and non-smokers, 32 we also examined for possible differential effects of alcohol consumption by smoking status in this study. We were also able to adjust for other factors which could be potential confounders in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake is an important factor in modulating the nutritional status of pulmonary tuberculosis patients, and may ultimately affect the outcome of pulmonary tuberculosis treatment. Previous studies reported the association between dietary intake and the infection risk of pulmonary tuberculosis [7][8][9]. However, no effective adjunctive nutritional therapy is available for the treatment of pulmonary tuberculosis treatment.…”
Section: Of 11mentioning
confidence: 99%